Beneficial effects of Urtica dioica on scopolamine-induced memory impairment in rats: protection against acetylcholinesterase activity and neuronal oxidative damage. (4th March 2019) - Ghasemi, Simagol; Moradzadeh, Malihe; Hosseini, Mahmoud; Beheshti, Farimah; Sadeghnia, Hamid Reza
Abstract: This study was conducted to investigate protective effects of Urtica dioica extract on acetylcholinesterase (AChE) activity and the oxidative damage of brain tissues in scopolamine-induced memory impairment model. The rats were treated with (1) saline (control), (2) scopolamine, and (3–5) the plant extract (20, 50, or 100 mg/kg) before scopolamine. The traveled distance and the latency to find the platform in Morris water maze (MWM) by scopolamine-treated group were longer while the time spent in target quadrant was shorter than those of the control. Scopolamine decreased the latency to enter the dark in passive avoidance test. Besides, it also increased AChE activity and malondialdehyde (MDA) concentration in the hippocampal and cortical tissues while decreased thiols content and superoxide dismutase (SOD) and catalase (CAT) activities in the brain ( p < 0.01– p <0.001). Treatment by the extract reversed all the effects of scopolamine ( p < 0.05– p <0.001). According to the results of present study, the beneficial effects of U. dioica on memory can be attributed to its protective effects on oxidative damage of brain tissue and AChE activity.